Analisis Makna Membohongi Diri pada Lirik Lagu - Suci Puji Lestari; Alex Sobur (UNISBA Press, 2023)
Abstract. The arrival of music in one's life is nothing new. Every region and culture in the world has certain music that is spoken, heard, or played at an event or historical event and in one's life journey. A songwriter can interact with his listeners with a song. Because with song lyrics, the writer can express himself about events that are happening in the world. In their creation, the songwriters use their language creativity in taking diction and integrating phenomena in society and the natural surroundings. Musicians have some meaning in arranging their lines and verses in this way, as well as their use of words, symbols, metaphors, etc. Lyrics or lyrics made by a musician must have meaning because the words used by musicians are a form of emotional expression contained in sound and words. One of Indonesia's indie musicians is Fiersa Besari, who started his career in 2021. His name skyrocketed in 2013. Then collaborated with Feby Putri and created a song called